2020
DOI: 10.1177/0146167220960270
|View full text |Cite
|
Sign up to set email alerts
|

Inconceivable Middle-Class Black Space: The Architecture and Consequences of Space-Focused Stereotype Content at the Race–Class Nexus

Abstract: White Americans tend to stereotype a Black neighborhood as lower class and less desirable than a similar White neighborhood. A strong mental image of Black areas, in general, as lower class and undesirable contributes to this perceptual race-gap. The present studies show that a weak mental image of middle-class Black space as middle class and desirable may also contribute. First, stereotype content analyses reveal how Whites’ diffuse mental image of middle-class Black space— rundown, suburban, clean, crime-rid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…It is thus possible that people perceive middle-class Black (vs. White) space as lower class and less desirable in part because they lack a well-formed middle-class Black space subtype. Indeed, emerging research shows that Whites’ mental image of middle-class Black (vs. White) space is less coherent and more likely to include negative characteristics (e.g., overpopulated; Yantis & Bonam, 2018). Therefore, in addition to holding a strong and coherent lower-class Black space prototype, Whites demonstrate a weak and incoherent middle-class Black space subtype, which could further dampen the likelihood that they will incorporate counterstereotypic class information into their perception of Black spaces.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus possible that people perceive middle-class Black (vs. White) space as lower class and less desirable in part because they lack a well-formed middle-class Black space subtype. Indeed, emerging research shows that Whites’ mental image of middle-class Black (vs. White) space is less coherent and more likely to include negative characteristics (e.g., overpopulated; Yantis & Bonam, 2018). Therefore, in addition to holding a strong and coherent lower-class Black space prototype, Whites demonstrate a weak and incoherent middle-class Black space subtype, which could further dampen the likelihood that they will incorporate counterstereotypic class information into their perception of Black spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that, compared to evaluations of those without HIV/AIDS, the participants' evaluations of the living spaces of PLWHA were more negative in terms of community evaluation and community-approaching willingness. Unlike previous research focused on Black Americans (e.g., Bonam et al, 2016;Yantis and Bonam, 2021), this study investigated the space-focused stereotype and its corresponding influence on cognition and behavioral inclinations in another social group with concealable stigma. Although it seems unlikely that people can distinguish PLWHA from non-infected people by appearance, geographical segregation between them does exist worldwide (e.g., Zulu et al, 2014;Jeefoo, 2016;Chávez, 2021), including as in China (Qin, 2017;Qiao et al, 2019;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect lies in the explicit measures of space-focused stereotypes. When measuring the space-focused stereotype and community evaluation of PLWHA, we mainly constructed the items from the view of socio-economic status based on previous literature (Bonam et al, 2016;Yantis and Bonam, 2021). However, we could not simply conclude that space-focused stereotypes of PLWHA only exist in terms of economic-related community evaluations.…”
Section: Limitations and Further Directionsmentioning
confidence: 99%
See 2 more Smart Citations